1997
DOI: 10.1016/s0140-6736(96)10488-8
|View full text |Cite
|
Sign up to set email alerts
|

Randomised study of effect of ibopamine on survival in patients with advanced severe heart failure

Abstract: Randomised study of effect of ibopamine on survival in patients with advanced severe heart failure Hampton, J.R.; Veldhuisen, D.J.; Kleber, F.X.; Cowley, A.J.; Ardia, A.; Block, P.; Cortina, A.; Cserhalmi, L.; Follath, F.; Jensen, G.; Kayanakis, J.; Lie, K.I.; Mancia, G.; Skene, A.M. Published in: Lancet DOI:10.1016/S0140-6736(96)10488-8 Link to publicationCitation for published version (APA): Hampton, J. R., Veldhuisen, D. J., Kleber, F. X., Cowley, A. J., Ardia, A., Block, P., ... Skene, A. M. (1997). Random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
5

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(60 citation statements)
references
References 10 publications
1
54
0
5
Order By: Relevance
“…RCT was stopped early after 1906 patients were enrolled, because of a 28% relative increase in mortality with ibopamine compared with placebo [17]. A physiological study demonstrated beta-blockers result in a decline in ejection fraction and increases in end-diastolic volume in patients with prior myocardial infarction [18].…”
Section: Hierarchies Of Research Evidencementioning
confidence: 99%
“…RCT was stopped early after 1906 patients were enrolled, because of a 28% relative increase in mortality with ibopamine compared with placebo [17]. A physiological study demonstrated beta-blockers result in a decline in ejection fraction and increases in end-diastolic volume in patients with prior myocardial infarction [18].…”
Section: Hierarchies Of Research Evidencementioning
confidence: 99%
“…Parece ser uma resposta de grupo, pois estudos com dopamina, dobutamina, anrinone, miorinone, vesnarinone, ibopamina etc. mostraram aumento de mortalidade 5,[50][51][52][53][54] .…”
Section: Tratamento Clínicounclassified
“…A despeito da melhora hemodinâmica e aumento da capacidade funcional [9][10][11][12][13] , a administração crônica desses agentes resultou, invariavelmente, em aumento da mortalidade [14][15][16][17][18] . Cabe ressaltar, por exemplo, o estudo PROMISE, que avaliou o uso de milrinone, um inibidor da fosfodiesterase por via oral, em mais de 1000 pacientes com IC classe funcional (CF) III e IV, e demonstrou um aumento de 28% na taxa de mortalidade no grupo de pacientes em uso da droga, quando comparados ao grupo que recebeu placebo 15 .…”
Section: Paradigmas Atuaisunclassified
“…Cabe ressaltar, por exemplo, o estudo PROMISE, que avaliou o uso de milrinone, um inibidor da fosfodiesterase por via oral, em mais de 1000 pacientes com IC classe funcional (CF) III e IV, e demonstrou um aumento de 28% na taxa de mortalidade no grupo de pacientes em uso da droga, quando comparados ao grupo que recebeu placebo 15 . Mais recentemente, o ensaio PRIME II avaliou a administração do agonista dopaminérgico de uso oral, ibopamina, comparado ao uso de placebo 14 . Esse ensaio foi suspenso pelo comitê de monitorização de segurança por aumento de mortalidade no grupo que recebeu a droga.…”
Section: Paradigmas Atuaisunclassified